Overeducation wage penalty among Ph.D. holders. An unconditional quantile regression analysis on Italian data - Giuseppe Lucio Gaeta; Giuseppe Lubrano Lavadera; Francesco Pastore (Global Labor Organization (GLO), 2018)
The wage effect of overeducation has only recently been investigated in the case of Ph.D. holders. The existing contributions rely on OLS estimates that allow measuring the average effect of being educationally mismatched at the mean of the conditional wage distribution. This paper, instead, observes the heterogeneity of the overeducation penalty along the hourly wage distribution and according to the study field and sector of employment (academic/non-academic) of Ph.D. holders. We estimate a Recentered Influence Function. The results reveal that overeducation hits the wages of those Ph.D. holders who are employed in the academic sector and in non-R&D jobs outside of the academic sector. Instead, no penalty exists among those who carry out R&D outside the Academia. The size of the penalty is higher among those who are in the mid-top of the wage distribution and hold a Social Science and Humanities specialization.
Keywords: C26; I23; I26; J13; J24; J28; 330; Job-education mismatch; Overeducation; Wages; Ph.D. holders; Unconditional quantile regression; Italy